Temporal changes in the spatial distribution of native forest fragments in the Eastern Ridges of Bogotá : implications for conservation (2003)
Geographic Information Systems and aerial photography were used to document temporal and spatial changes in landscape patterns of native forests in the Eastern ridges of Bogotá, and to identify areas to preserve these forests. Landscape patterns were quantified for Six years between 1940 and 1998. Forest fragmentation was revealed as an increase in the homogeneity of the spatial distribution of the native forest remnants. Patchiness decreased in the native forest landscape along the 58-year period because of patches disappearance, and total area decreased significantly from about 325 ha in 1955 to 54 ha in 1982. A slight increase was observed in 1998, due to strict measures adopted by the local government to preserve the native forest. Existing native forest patches and nearby areas that were no longer covered by forest were considered as potential areas for conservation. Other conservation areas were identified using a predictive model based on suitable environmental conditions for forest growth. Since the native forest landscape of the Eastern ridges has been severely affected by human activities, the predictive model was proposed as a tool in conservation decision-making because of possible inclusion of new parameters as new data become available.